Cerebellar contributions to neurological soft signs in healthy young adults - Hirjak, Dusan; Thomann, Philipp; Kubera, Katharina Maria; Stieltjes, Bram; Wolf, Robert Christian (European archives of psychiatry and clinical neuroscience, 2016)
Neurological soft signs (NSS) are frequently found in psychiatric disorders of significant neurodevelopmental origin, e.g., in patients with schizophrenia and autism. Yet NSS are also present in healthy individuals suggesting a neurodevelopmental signature of motor function, probably as a continuum between health and disease. So far, little is known about the neural mechanisms underlying these motor phenomena in healthy persons, and it is even less known whether the cerebellum contributes to NSS expression. Thirty-seven healthy young adults (mean age = 23 years) were studied using high-resolution structural magnetic resonance imaging (MRI) and “resting-state” functional MRI at three Tesla. NSS levels were measured using the “Heidelberg Scale.” Cerebellar gray matter volume was investigated using cerebellum-optimized voxel-based analysis methods. Cerebellar function was assessed using regional homogeneity (ReHo), a measure of local network strength. The relationship between cerebellar structure and function and NSS was analyzed using regression models. There was no significant relationship between cerebellar volume and NSS (p < 0.005, uncorrected for height, p < 0.05 corrected for spatial extent). Positive associations with cerebellar lobule VI activity were found for the “motor coordination” and “hard signs” NSS domains. A negative relationship was found between lobule VI activity and “complex motor task” domain (p < 0.005, uncorrected for height, p < 0.05 corrected for spatial extent). The data indicate that in healthy young adults, distinct NSS domains are related to cerebellar activity, specifically with activity of cerebellar subregions with known cortical somatomotor projections. In contrast, cerebellar volume is not predictive of NSS in healthy persons.